A 1D silver(I) coordination polymer of a new hydrozone-hydrazide ligand: Spectral, structural, emission, and anti-bacterial properties and its application as a solid source precursor for silver oxide nanoparticles. (January 2022) - Selvam, Pitchai; Antharjanam, Sudhadevi; Srinivasan, Krishnan; Premkumar, Thathan
Abstract: A new one-dimensional (1D) coordination polymer of composition [Ag(L)(NO3 )]n was synthesized by a reaction of silver(I) nitrate with a new hydrazone-hydrazide ligand (L) derived from 2-acetyl furan and ethyl hydrazine carboxylate. Both the ligand, L, and the silver(I) complex were characterized using elemental analysis, electron impact mass spectrometry (EI-Mass), infrared (IR), proton nuclear magnetic resonance ( 1 H NMR), ultraviolet–visible (UV–Vis) spectroscopy, and emission spectroscopy analyses. Single-crystal X-ray diffraction study shows that the structure of the silver(I) complex consists of 1D polymeric chains in which silver(I) ion is in four coordination complexes arising from one N, O-chelating L and two O, O′-bridging nitrate anions. The complex emitted energy around 360 nm and was used as a single precursor for synthesis of silver oxide nanoparticles (Ag2 O NPs). From transmission electron microscopy (TEM) and higher-resolution TEM (HR-TEM) images, the as-prepared Ag2 O NPs were nearly spherical in shape with average particle sizes of approximately 22–24 nm. Anti-bacterial properties of both the ligand and the metal complex were studied. Graphical abstract: Image 1 Highlights: A new hydrazone-hydrazide type ligand has been prepared. A 1D silver(I) coordination polymer complex was introduced. The complex was used as a solid source precursor to prepare nano sized Ag2 O. The complex exhibited emission and antibacterial properties.